Some Reflections on Educated Mothering. (October 2019) - Panda, Gayatri
On the basis of interviews of a total of 75 mothers belonging to varied socio-economic backgrounds in a village in Odisha, this article argues that educated mothers play an active role in family decision-making processes that relate to daughters' education and future career paths. From the early school years of their children, educated mothers use their informed experiences to sketch future career paths. The views of mothers on children's present schooling and their ideas about further education and occupation plans are discussed. The present exploratory empirical village study finds that irrespective of their caste origins, the educational attainment of mothers brings a change in their outlook, gives them confidence to guide children's schooling and participate in the family decision-making processes on education and career goals.